Crafty design of chemical bonding to construct MoO2/CdS nanorod photocatalysts for boosting hydrogen evolution. (13th September 2019) - Gao, Fan; Huang, Xueyan; Zhang, Lulu; Zhao, Yan; Feng, Wenhui; Liu, Ping
Abstract: An efficient MoO2 /CdS photocatalyst has been successfully constructed by a relatively facile way to construct a specific combination mode through chemical bond, which results in strong interaction between MoO2 nanoparticles and CdS nanorods. X-ray photoelectron spectroscopy further confirms the formation of Mo–S bonding, which acts as a connection bridge and develops an intimate contact between CdS-NRs and MoO2 nanoparticles. Benefitting from the synergic effect of the enhancement on the light absorption, carriers' efficient separation and lower the overpotential of hydrogen evolution, the obtained MoO2 /CdS composite has shown an excellent enhancement in photocatalytic H2 generation and the optimal H2 evolution rate reaches as high as 30 times than that of pure CdS nanorods. We have experimentally shed light on the mechanism of this excellent enhancement performance in detail. Moreover, our work can broaden the construction and the application of developing other efficient photocatalytic material containing transition metal oxide. Highlights: MoO2 /CdS photocatalyst with chemical bonding Mo–S has been synthesized through a mild method. The MoO2 /CdS composites show largely enhanced photocatalytic performance for water splitting. This strategy can obliterate the passivation layer, leading to more active sites exposed on MoO2 . A possible mechanism of this enhancement for H2 evolution is given.